Discourse Markers Activate Their, Like, Cohort Competitors. Issue 9 (21st October 2021) - Bosker, Hans Rutger; Badaya, Esperanza; Corley, Martin
ABSTRACT: Speech in everyday conversations is riddled with discourse markers (DMs), such as well, you know, and like . However, in many lab-based studies of speech comprehension, such DMs are typically absent from the carefully articulated and highly controlled speech stimuli. As such, little is known about how these DMs influence online word recognition. The present study specifically investigated the online processing of DM like and how it influences the activation of words in the mental lexicon. We specifically targeted the cohort competitor (CC) effect in the Visual World Paradigm: Upon hearing spoken instructions to "pick up the beaker, " human listeners also typically fixate—next to the target object—referents that overlap phonologically with the target word (cohort competitors such as beetle ; CCs). However, several studies have argued that CC effects are constrained by syntactic, semantic, pragmatic, and discourse constraints. Therefore, the present study investigated whether DM like influences online word recognition by activating its cohort competitors (e.g., lightbulb ). In an eye-tracking experiment using the Visual World Paradigm, we demonstrate that when participants heard spoken instructions such as "Now press the button for the, like … unicycle, " they showed anticipatory looks to the CC referent ( lightbulb) well before hearing the target. This CC effect was sustained for a relatively long period of time, even despite hearing disambiguating information (i.e., the /k/ in like ). Analysis of the reaction times also showed that participants were significantly faster to select CC targets ( lightbulb ) when preceded by DM like . These findings suggest that seemingly trivial DMs, such as like, activate their CCs, impacting online word recognition. Thus, we advocate a more holistic perspective on spoken language comprehension in naturalistic communication, including the processing of DMs.